2001
DOI: 10.1107/s0907444901014524
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of catalytic function by molecular association: structure of phospholipase A2fromDaboia russelli pulchella(DPLA2) at 1.9 Å resolution

Abstract: The crystal structure of phospholipase A 2 from the venom of Daboia russelli pulchella has been re®ned to an R factor of 0.216 using 17 922 re¯ections to 1.9 A Ê resolution. The structure contains two crystallographically independent molecules in the asymmetric unit. The overall conformations of the two molecules are essentially the same except for three regions, namely the calcium-binding loop including Trp31, the -wing and the C-terminal residues 119±131. Although these differences have apparently been cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 18 publications
3
38
0
Order By: Relevance
“…As reported previously (Chandra et al, 2001), two molecules of DPLA 2 were found to be strongly associated in both crystalline and solution states even at very low concentrations. However, every new preparation of DPLA 2 was examined for molecular association using the DLS system (Dlerks & Partner, Hamburg, Germany) and analyzed using the software described by Schulze (1996).…”
Section: Dynamic Light Scattering (Dls)supporting
confidence: 84%
See 2 more Smart Citations
“…As reported previously (Chandra et al, 2001), two molecules of DPLA 2 were found to be strongly associated in both crystalline and solution states even at very low concentrations. However, every new preparation of DPLA 2 was examined for molecular association using the DLS system (Dlerks & Partner, Hamburg, Germany) and analyzed using the software described by Schulze (1996).…”
Section: Dynamic Light Scattering (Dls)supporting
confidence: 84%
“…Both of these effects in DPLA 2 can be caused by the association of two molecules. Indeed, it has been shown by earlier studies (Chandra et al, 2000(Chandra et al, , 2001) that the association of two molecules converts the binding site of molecule A, which is located at the interface, into a suitable form of conformation for the binding of ligands, but not the binding site of molecule B. These studies have also shown that the surface-exposed hydrophobic channel in molecule B seems to be completely unin¯uenced by the association and hence the observed unsuitable conformation of the hydrophobic channel may be an inherent property of DPLA 2 .…”
Section: Inhibition Of Pla 2 By the Peptide Laiysmentioning
confidence: 80%
See 1 more Smart Citation
“…It may be emphasized that the peptide FLSYK forms a larger number of interactions with PLA 2 as compared with those observed in other complexes formed between PLA 2 and synthetic/natural inhibitors reported earlier (10,11,(13)(14)(15)(16)(37)(38)(39)(40)(41) making it to be the strongest inhibitor known so far against PLA 2 . Its dissociation constant, K d was found to be 3.57 Ϯ 0.05 ϫ 10 Ϫ9 M. Recently, molecular modeling studies showing the binding of FLSYK to human sPLA 2 -IIA were also reported (19).…”
Section: Resultsmentioning
confidence: 97%
“…The structure of PLA 2 from Daboia russelli pulchella has been studied in its native form (24) and in the complexed forms with natural substances such as ␣-tocopherol (39) and aristolochic acid (40), and with a designed peptide inhibitor Leu-Ala-IleTyr-Ser (LAIYS) (41). In all these structures, PLA 2 exists in the form of an asymmetric dimer.…”
Section: Comparison Of the Structures Of Pla 2 In The Present Complexmentioning
confidence: 99%